2021
DOI: 10.1111/jsr.13513
|View full text |Cite
|
Sign up to set email alerts
|

How does work impact daily sleep quality? A within‐individual study using actigraphy and self‐reports over the retirement transition

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Participants with consistent daily patterns also often reported methods of enhancing their environment in preparation for sleep, along the principles of sleep hygiene [ 22 ]; these participants reported turning the television off at a pre-determined time, not staying up for no particular reason, not having any screen stimulation in the bedroom and reducing time on the computer or tablet in the hours before bed. Television viewing and computer/screen usage before bed may be biologically significant as blue-wavelength light emitted from these devices may suppress melatonin synthesis and delay sleep onset [ 8 , 23 ]. As previous work has indicated that sleep hygiene is useful in the management of chronic conditions such as type 2 DM [ 24 ], the current results indicate that increased psychoeducation around good sleep habits may be useful in disease management, especially as a number of participants noted that sleep was not discussed during their routine clinical care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants with consistent daily patterns also often reported methods of enhancing their environment in preparation for sleep, along the principles of sleep hygiene [ 22 ]; these participants reported turning the television off at a pre-determined time, not staying up for no particular reason, not having any screen stimulation in the bedroom and reducing time on the computer or tablet in the hours before bed. Television viewing and computer/screen usage before bed may be biologically significant as blue-wavelength light emitted from these devices may suppress melatonin synthesis and delay sleep onset [ 8 , 23 ]. As previous work has indicated that sleep hygiene is useful in the management of chronic conditions such as type 2 DM [ 24 ], the current results indicate that increased psychoeducation around good sleep habits may be useful in disease management, especially as a number of participants noted that sleep was not discussed during their routine clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Greater social jetlag may be important for metabolic health as it has been associated with obesity and type 2 diabetes risk and severity [ 3 , 4 , 5 , 6 ]. The original conception of social jetlag as impacting people during their working life [ 7 ] is challenged by recent research showing that social jetlag persists to some degree after retirement [ 8 , 9 , 10 ]. The factors driving social jetlag in retirement are unclear, as the same working time constraints do not pertain to retirees as for younger age groups; however, it is important to note that social zeitgebers, including social interaction and personal relationships, may influence circadian rhythms and sleep timing [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Model 1 looks at the relationship between employment status and sleep quality and duration, whilst Model 2 selected the working population (employment or self-employment) and looks at the relationship between sleep quality and duration and working and job satisfaction. The employment status contains 13 modalities that distinguish different positions within and outside the labour market on which information was collected in the survey: (1) employed full-time, (2) company executive, (3) employed parttime, (4) employed under contract, (5) temporary employed, (6) employed other, (7) owner of independent business, (8) help in independent business, ( 9) side job at home, (10) retired, (11) not retired -receiving medical care, (12) keeping house (13) inactive for other reasons. The first modality (employed full-time) -that is the most represented among the working population -is selected as the reference category.…”
Section: Employment Status Working Time and Job Satisfactionmentioning
confidence: 99%
“…A substantial amount of research was produced on the relationship between transition from work to retirement and sleep quality and duration using longitudinal data. It was shown that retirement is not only associated with short-term reductions in sleep difficulties but also increase in sleep duration over 1 to 2 years 12,13 . Results are similar using panel data from France 14 .…”
Section: Introductionmentioning
confidence: 99%